(untitled) (Bangladesh Journal of Medicine, 2024)
As an endemic zone, malaria and dengue coinfection can be expected in Bangladesh, although there have not been enough case reports of such coinfection. We describe a previously healthy 22-year-old male from Dhaka, with a history of travelling to Coxs-Bazar 3 weeks ago, presented with fever with chills and rigors, generalized weakness and cough for 2 weeks. Clinical examination showed tachycardia, hypotension, subconjunctival haemorrhage and positive tourniquet test. Lab reports showed NS1-Ag positive, thrombocytopenia, progressive anaemia, mild hyperbilirubinemia. He was treated initially for dengue haemorrhagic fever. His laboratory parameters started improving; however, he had persistent fever with chills and rigors daily and persistent coughing. Peripheral smear for Malaria showed schizonts and trophozoites of Plasmodium falciparum and ICT for malaria was positive. He recovered following treatment with IV fluids and oral artesunate. The presence of fever even in a critical phase of dengue, the typical rise of temperature daily, progressive anaemia, mild jaundice and specific travelling history gave a clue of coinfection with Malaria. On follow-up, after 2 weeks, he had no symptoms, and all the laboratory parameters were normal. challenge was the atypical features like dry cough and exertional dyspnoea. The timely diagnosis and appropriate treatment were crucial for prognosis of this patient. Bangladesh J Medicine 2024; 35(1): 38-41